2019
DOI: 10.21203/rs.2.11842/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carriage Rate of Neisseria meningitidis, Antibiotic Susceptibility Pattern and Associated Risk Factors among Primary School Children in Gondar town, Northwest Ethiopia

Abstract: Background Invasive meningococcal disease has 70–80% mortality. Globally, 1.2 million estimated cases were reported with ~135,000 deaths annually. In African meningitis belt bacterial meningitis remains a serious threat to health accounting an estimated 500,000 cases of invasive meningococcal disease annually.In Ethiopia, specifically in our study area, limited information is found on the oropharyngeal carriage, antimicrobial resistance pattern and associated risk factors for N. meningitidis especially in sch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
3
0
0
Order By: Relevance
“…However, alcohol drinking and party attendance often occur simultaneously, making the causal relationship with carriage hard to assess. Previous tonsillectomy has been associated with higher carriage rates of N. meningitidis in other studies [31, 32], and this association was also seen in the present study. We studied one possible risk factor for meningococcal carriage that has been only sparsely studied before: the use of Swedish snus.…”
Section: Discussionsupporting
confidence: 91%
“…However, alcohol drinking and party attendance often occur simultaneously, making the causal relationship with carriage hard to assess. Previous tonsillectomy has been associated with higher carriage rates of N. meningitidis in other studies [31, 32], and this association was also seen in the present study. We studied one possible risk factor for meningococcal carriage that has been only sparsely studied before: the use of Swedish snus.…”
Section: Discussionsupporting
confidence: 91%
“…Another independently associated factor statically associated with nasopharyngeal bacteria carriage was children with a history of hospitalization [AOR=4.08, 95%CI 1.45–1.53, P=0.008]. This is in agreement with the studies conducted in Ethiopia, Hawassa (p=0.00) [ 55 ], Gondar (P= 0.031) [ 71 ]. Common type of nosocomial infection involves invasive devices and procedures (urinary catheters, central lines, mechanical ventilation, or surgery) which might be an important factor for the transmission of respiratory infections and it could have a role in bacteria carriage for healthy individuals [ 72 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study participants who had large family-size showed statistically significant association with the occurrence of with nasopharyngeal bacteria carriage [AOR=2.17, 95%CI 1.24–3.81, P=0.006], which is comparable with studies reported in Indian (P = 0.03)[ 70 ], Iran (p=0.044) [ 62 ], Ethiopia in Addis Ababa (p=0.006) [ 7 ], and Gondar (P= 0.031) [ 71 ]. The other factor in the present study that has statically significant association was numbers of rooms (1-2) per house with [AOR=5.88, 95%CI: 1.26-27.57, P=0.024].…”
Section: Discussionsupporting
confidence: 69%